Seamless and secure communications over heterogeneous wireless networks - Cao, Jiannong (SpringerBriefs in Computer Science, 2014)
This brief provides an overview of the requirements, challenges, design issues and major techniques for seamless and secure communications over heterogeneous wireless networks. It summarizes and provides detailed insights into the latest research on handoff management, mobility management, fast authentication and security management to support seamless and secure roaming for mobile clients. The reader will also learn about the challenges in developing relevant technologies and providing ubiquitous Internet access over heterogeneous wireless networks. The authors have extensive experience in implementing such technologies over heterogeneous wireless networks, thus enabling them to bridge the gap between the theoretical results of research and the real practice. Combining basic theoretical concepts and practical implementation, this brief is ideal for professionals and researchers in the field. Advanced-level students interested in computer communication networks and wireless technologies will also find the content helpful.